Solar Cell Performance Test against Load Variations - Sumarno, F Gatot; Wahyono, Wahyono; Mei Hermawan, Baktiyar; Hamim Su”™udy, Ahmad; Fatowil Aulia, Nur; Khoiroh, Ikhwatinah; Surindra, Mochammad Denny (Eksergi, 2022)
Solar cell is a converter of light energy into electrical energy. This study aims to examine the characteristics of the solar cell to load variations. The research was conducted at the Semarang State Polytechnic Energy Conversion Lab. The solar cell used in the research of the monocrystalline solar cell type KTENG CP-520S. The research method is carried out by measuring the value of solar intensity, voltage and electric current from the solar cell, then calculating the value of the power and efficiency of the solar cell. The greater the intensity of sunlight, the better the characteristics of the solar cell with a note that the solar cell surface temperature must be stable at 250C. The results showed that the highest input power of the solar cell was 5293.69 watts at a lamp load of 115 watts at 833.6 W/m2 of radiation during sunny weather. The highest value of the output power of the solar cell is 191.52 watts when the lamp is loaded with 190 watts of radiation at 739.4 W/m2 during sunny weather. While the highest value of the load output power is 212.43 watts when the lamp is loaded with 200 watts of radiation at 724.4 W/m2 when the weather is sunny. The highest efficiency of the solar cell is 4.13% when the lamp is loaded with 200 watts of radiation at 724.4 W/m2 when the weather is sunny. And the highest value of Solar Power Plant efficiency is 4.61% at a 200 watt lamp loading at 724.4 W/m2 radiation when the weather is sunny.